Molecular detection of different virulence factors genes harbor pslA, pelA, exoS, toxA and algD among biofilm-forming clinical isolates of Pseudomonas aeruginosa: Molecular detection of virulence factors of P. aeruginosa - Farhan, Rehab E.; Solyman, Samar M; Hanora, Amro M; Azab, Marwa M (Cellular and Molecular Biology, 2023)
Pseudomonas aeruginosa (P. aeruginosa) is considered as the foremost cause of hospital-acquired infections due to its innate and plasmid-mediated resistance to multiple antibiotics making it a multi-drug resistant (MDR) pathogen. This study aimed to determine the biofilm formation ability and the presence of different virulence factors genes (pslA, pelA, exoS, toxA and algD) among biofilm-forming strains of P. aeruginosa clinical isolates from burn units in Ismailia Hospitals, Egypt. In our cross-sectional study, one hundred and twenty-six (126) non-duplicate clinical P. aeruginosa isolates were recovered from 450 clinical specimens from burn units in Ismailia Hospitals. The antibiotic sensitivity of strong and moderate biofilm producer isolates was investigated using the disc diffusion method. The isolated bacteria were tested for their ability to form biofilm using a microtiter plate assay. The expression of (pslA, pelA, exoS, toxA and algD) genes in biofilm producers isolates was detected using PCR. The MPA detected 80% (95 /126) isolates as biofilm producers, 18% (22/126) were strong biofilm producers, 34% (43/126) were moderate biofilm producers, 28% (35/126) were weak biofilm producers and 20% (31/126) non-biofilm producers. Susceptibility pattern analysis of biofilm-forming P. aeruginosa isolates (95) detected that 60% (68/ 95) were multi-drug resistant isolates (MDR). Resistance to all used antibiotics and multidrug resistance was higher among biofilm-producing than non-biofilm-producing strains, but the difference was statistically non-significant. Investigation of virulence factors associated genes revealed that 96%, 94%, 86.4%, 80.0% and 74% of the biofilm producers isolates were harboring algD, pslA, pel A, toxA and exoS gene, respectively. The present study confirmed that antimicrobial resistance and virulence genes were more prominent in biofilm-producing P. aeruginosa than in non-biofilm-producers.